Microaneurysms visualisation using five different optical coherence tomography angiography devices compared to fluorescein angiography. Issue 4 (11th June 2020) - Parrulli, Salvatore; Corvi, Federico; Cozzi, Mariano; Monteduro, Davide; Zicarelli, Federico; Staurenghi, Giovanni
Abstract : Background: To compare fluorescein angiography (FA) and five different optical coherence tomography angiography (OCTA) devices and to test their reproducibility in the evaluation of retinal microaneurysms (MAs) secondary to diabetic retinopathy (DR). Methods: On the same day, patients with DR were imaged with FA and five OCTA devices: prototype Spectralis OCTA, prototype PlexElite, RTVue XR Avanti, AngioPlex and DRI OCT Triton. For all OCTA devices, a 3×3 volume scan pattern was performed. MAs were evaluated for the superficial capillary plexus (SCP) and deep capillary plexus (DCP). Results: Twenty eyes of 15 patients with DR were included. FA counted a significantly higher number of MAs compared to OCTA devices. Spectralis OCTA obtained a significantly higher number of MAs compared to PlexElite, RTVue XR Avanti, AngioPlex and DRI OCT Triton (p<0.0001). PlexElite and AngioPlex showed a greater number of MAs in the SCP, Spectralis OCTA, RTVue XR Avanti and DRI OCT Triton in the DCP. Higher sensitivity (43.3%) but lowest specificity (54.4%) was observed for Spectralis OCTA compared to other devices. The higher specificity (78.5%) and positive predictive value (83.3%) were observed for DRI OCT Triton. Conclusions: FA remains the best imaging modality to visualise retinal MAs. Spectralis OCTA was able to detect more MAs compared to other devices, likely due to the higher number of B-scans in the scanned area as well as due to the higher number of repeated B-scans. The high variability between OCTA devices should be taken into account for future clinical trials as in clinical practice.